Theoretical Principles of Researching Diminutive - Mintsys, E.; Mintsys, Yu. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article presents a survey of the diminutive-related researches and considers diminutive on all the language levels (morphological, lexical and syntactical). It analyzes the principal theories of the development of diminutive’s semantics and draws a distinction line between ‚smallness‛ and ‚diminutive‛. Diminutive is viewed versus augmentative and is presented as a conceptual category, a system of semantic criteria which collectively denote diminution of objective characteristics of an object